2023
DOI: 10.1371/journal.pone.0287738
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine reduces T cells activation recall antigen responses

Abstract: Background In the context of the current COVID-19 pandemic, there is still limited information about how people suffering from autoimmune diseases respond to the different COVID vaccines. The fact that they are taking an immunosuppressant or other drugs that aim to decrease the immune system activities, such as hydroxychloroquine (HCQ), could also impact their ability to respond to a COVID vaccine and vaccines in general. Methods Heathy donors were given 200mg of HCQ daily for 6-weeks to assess HCQs impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Another mechanism through which HCQ could affect Th17/Treg ratio is by inhibiting autophagy in both cell populations. In experiments with rodents and PBMC isolated from SLE and HIV patients, HCQ attenuated Th17 differentiation, proliferation, and production of IL-17 while promoting the immunosuppressive effect of Tregs ( Piconi et al, 2011 ; An et al, 2017 ; Yang et al, 2018 ; Kowatsch et al, 2023 ). Due to that, An et al suggested that HCQ might have different effects of autophagy on diverse T-cell subsets ( An et al, 2017 ).…”
Section: Adaptive Immune System In Pe and Hcq Immunomodulatory Proper...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism through which HCQ could affect Th17/Treg ratio is by inhibiting autophagy in both cell populations. In experiments with rodents and PBMC isolated from SLE and HIV patients, HCQ attenuated Th17 differentiation, proliferation, and production of IL-17 while promoting the immunosuppressive effect of Tregs ( Piconi et al, 2011 ; An et al, 2017 ; Yang et al, 2018 ; Kowatsch et al, 2023 ). Due to that, An et al suggested that HCQ might have different effects of autophagy on diverse T-cell subsets ( An et al, 2017 ).…”
Section: Adaptive Immune System In Pe and Hcq Immunomodulatory Proper...mentioning
confidence: 99%
“…Furthermore, the percentages of plasma cells generated upon in vitro stimulation with CpG were significantly higher in the PE group than in the control group ( Liao et al, 2009 ). These cells present another potential target for HCQ since HCQ effectively suppresses the class-switch of memory B cells to plasma cells and also decreases the production of IgG ( Torigoe et al, 2018 ; Kowatsch et al, 2023 ), both of which are increased in PE ( Liao et al, 2009 ).…”
Section: Adaptive Immune System In Pe and Hcq Immunomodulatory Proper...mentioning
confidence: 99%
“…Mechanistically, HCQ suppresses T-and B-cell receptor mediated signalling by specifically inhibiting calcium signalling and subsequent NFAT (nuclear factor of activated T-cells) activation [108] . HCQ induces apoptosis in autoreactive memory T-cells [109] , and reduces pro-inflammatory T-cell activation [110,111] . 7.…”
Section: T-cells Play An Important Role In Immunopathogenesis Of Aavmentioning
confidence: 99%
“…(11)(26) (15) También junto con los antivirales se añadió los fármacos antimalárico, como cloroquina o hidrocicloroquina, que demostraron actividad antiviral in vitro. También ha demostrado reducir los niveles de anticuerpos antifosfolípidos y de las células T (CD95) (23) (14) La azitromicina es el antibiótico más usado durante el tratamiento para los pacientes con covid que presentaron infiltrado lobar en una radiografía de tórax, leucocitosis y niveles elevados de LDH sérico. Pero se relacionó con mayores eventos adversos cardiovasculares como insuficiencia cardiaca aguda, lesión renal aguda, insuficiencia respiratoria aguda, pero con un 6,6% riesgo de muerte con el tratamiento estándar.…”
Section: Abordaje Terapéuticounclassified